2020
DOI: 10.1016/j.redox.2019.101354
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase-derived extracellular nitric oxide flux regulates proinflammatory responses at the single cell level

Abstract: The role of nitric oxide (NO) in cancer progression has largely been studied in the context of tumor NOS2 expression. However, pro- versus anti-tumor signaling is also affected by tumor cell-macrophage interactions. While these cell-cell interactions are partly regulated by NO, the functional effects of NO flux on proinflammatory (M1) macrophages are unknown. Using a triple negative murine breast cancer model, we explored the potential role of macrophage Nos2 on 4T1 tumor progression. The effects of NO on macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 41 publications
(54 reference statements)
6
49
0
2
Order By: Relevance
“…Indeed, we can rescue MRC with blockade of iNOS during stimulation ( Supplementary Fig. 6E, F) and exposure to low dose of NO affects MRC but not basal OCR 53 . Therefore, we propose that, during stimulation, low NADH/NAD + due to NO-mediated blunting of mentioned enzymatic activities, promotes the accumulation of CI in D form facilitating degradation and favoring full glycolytic commitment.…”
Section: Discussionmentioning
confidence: 70%
“…Indeed, we can rescue MRC with blockade of iNOS during stimulation ( Supplementary Fig. 6E, F) and exposure to low dose of NO affects MRC but not basal OCR 53 . Therefore, we propose that, during stimulation, low NADH/NAD + due to NO-mediated blunting of mentioned enzymatic activities, promotes the accumulation of CI in D form facilitating degradation and favoring full glycolytic commitment.…”
Section: Discussionmentioning
confidence: 70%
“…It is important to note that the coatings containing ZnO nanoparticles, namely PCL-ZnO and PCL-CM-ZnO, predominantly showed a small-rounded morphology typical to unstimulated macrophages as noticed in the absence of LPS (TCPS (−)). However, even though the cellular morphology is seen as a characteristic of the inflammatory response towards the biomaterial [ 81 ], recent data revealed that a modified cell morphology does not necessarily indicate a strongly activated macrophage phenotype [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…by the release of NO and PGE2 from the cells 11 . Nos2-expressing cell clumps likely lead to significantly higher local concentrations of NO than could arise when Nos2-expressing cells are scattered and isolated 15 and thus augment this paracrine mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…11). Macrophages treated with the pro-inflammatory cytokines IFNγ and LPS express higher levels of Nos2 and thus produce more NO, which converts them to a glycolytic pathway and decreases their mitochondrial metabolism and O2 consumption 15 . This effect was observed in REECs as the hypoxic front of treated macrophages was further from the hole than that of untreated cells (Supplemental Fig.…”
mentioning
confidence: 99%